The association of dietary nitrates/nitrites intake and the gut microbial metabolite trimethylamine N-oxide and kynurenine in adults: a population-based study - Mirzababaei, Atieh; Mahmoodi, Maryam; Abaj, Faezeh; Barkhidarian, Bahareh; Dehghani, Azadeh; Khalili, Pardis; Roumi, Zahra; Mirzaei, Khadijeh (Frontiers in Nutrition, 2024)
Background Dietary nitrate and nitrite may affect the gut microbiota and its metabolites, such as trimethylamine N-oxide (TMAO) and kynurenine (KYN). However, this association and the exact mechanism are still unclear. Therefore, this study aimed to assess the association between dietary consumption of nitrite and nitrate on TMAO and KYN levels in adults. Methods This cross-sectional study was employed on a subsample baseline phase of the Tehran University of Medical Sciences (TUMS) Employee's Cohort Study (TEC). A total of 250 adults aged 18 years or older were included in the current analysis. Data on the dietary intakes were collected using a validated dish-based food frequency questionnaire (FFQ), and dietary intakes of nitrite and nitrate were estimated using the FFQ with 144 items. Serum profiles and TMAO and KYN were measured using a standard protocol. Results The findings of this study demonstrate a significant association between the intake of animal sources of nitrate and nitrite and the likelihood of having elevated levels of TMAO and KYN. Specifically, after adjustment, individuals with the highest intake adherence to nitrates from animal sources exhibited increased odds of having the highest level of TMAO (≥51.02 pg/ml) (OR = 1.51, 95% CI = 0.59–3.88, P = 0.03) and KYN (≥417.41 pg/ml) (OR = 1.75, 95% CI = 0.73–4.17, P = 0.02). Additionally, subjects with the highest animal intake from nitrite sources have 1.73 and 1.45 times higher odds of having the highest levels of TMAO and KYN. These results emphasize the potential implications of animal-derived nitrate and nitrite consumption on the levels of TMAO and KYN. Conclusion The present evidence indicates that a high level of nitrate and nitrite intake from animal sources can increase the odds of high levels of TMAO and KYN. Further studies suggest that we should better evaluate and understand this association.